EVOLUSI FONOLOGIS LEKSIKON DALAM SEJARAH PERKEMBANGAN BAHASA BALI - Putu Eka Guna Yasa; Aron Meko Mbete; Ni Made Dhanawaty (Program Magister Linguistik Universitas Udayana, 2018)
This research produced research in the language of the development of Balinese language. In the search for the texts of Bali Kuna's motion inscriptions, the Middle Balinese literary works, and Modern Balinese languages ??as the data source showed a relatively long period of time. In accordance with this problem, this study used comparative historical linguistic theory. Meanwhile, methodologically at the stage of providing data, it applied the observational method in the written data, and interview method for the oral Balinese language data. In the data analysis section, the method applied is equivalent to the basic technique of speech organ whispering (phonetic articulatory). The result of analysis showed that the phonological evoluted by the sign of sound changing. Thus, the changes found consisted of (1) sound absorption which theoretically included in afferesis, syncope, haplology; (2) metathesis; (3) unusual sounds; (4) vowels and consonants changing.